2010
DOI: 10.1111/j.1463-1318.2009.01833.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhoidectomy by vessel sealing system under local anaesthesia in an outpatient setting: preliminary experience

Abstract: LigaSure haemorrhoidectomy under local anaesthesia in the outpatient setting is safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…So generally less amount of thermal injury at the surgical site leads to decrease postoperative pain. 16 …”
Section: Discussionmentioning
confidence: 99%
“…So generally less amount of thermal injury at the surgical site leads to decrease postoperative pain. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Several results from this study suggested that after this treatment, pain rapidly reduces to a level where the patient can return to work on day 3, although it is intense immediately after treatment. First, the maximal pain score was 7.4, which is >6.2 that has been reported for common hemorrhoidectomy [6]. This increased pain may be because the ALTA injection itself caused pain, although it may have reduced pain from resection wounds.…”
Section: Discussionmentioning
confidence: 73%
“…Although, general or epidural anesthesia is the most commonly performed anesthetic techniques, local anesthesia (LA) is considered as a safe alternative with a significant reduction in complications (13)(14)(15). Ambulatory anorectal surgery is becoming a routine procedure for several proctologic diseases including fistula, abscess, condyloma, pilonidal disease, and hemorrhoids.…”
Section: Introductionmentioning
confidence: 99%